Formula Optimization of Fermented Hollow Noodles - Ting WANG; Chong LIU; Xueling ZHENG (Shipin gongye ke-ji, 2022)
Machine-made fermented hollow noodles are a new nutritious flavored noodle product that appeared in the market in recent years, however, the influence of the formula on the quality of machine-made fermented hollow noodles is still unclear. In this paper, the direct fermentation method was used to make fermented hollow noodles. The effects of different addition amounts of yeast, salt, and water in flour on the cooking characteristics, texture characteristics, and sensory quality of fermented hollow noodles were investigated by a single factor experiments. On this basis, the formula of fermentation hollow noodle was optimized by response surface Box-Behnken experiment. The results showed that the best formula for fermented hollow noodles was: Based on the quality of flour, the amount of yeast added was 0.83%, the amount of salt added was 0.64%, and the amount of water was 33.67%. The evaluating value of the fermented hollow noodles under the optimized conditions was 0.909, which was consistent with the evaluating value of 0.932 predicted by the model, indicating that its flavor was good, the taste was smooth, cooking and texture characteristics were excellent. The addition of salt and water had extremely significant effects on the chewiness of the fermented hollow noodles (P<0.01), the addition of yeast and water had a significant effect on the total sensory score (P<0.05), and the addition of salt had a very significant effect on the cooking loss (P<0.01). This research could provide theoretical and technical guidance for the production of machine-made fermented hollow noodles.